2020
DOI: 10.3390/ijms21238992
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metabolism in Bone Development and Homeostasis

Abstract: Carbohydrates, fats, and proteins are the underlying energy sources for animals and are catabolized through specific biochemical cascades involving numerous enzymes. The catabolites and metabolites in these metabolic pathways are crucial for many cellular functions; therefore, an imbalance and/or dysregulation of these pathways causes cellular dysfunction, resulting in various metabolic diseases. Bone, a highly mineralized organ that serves as a skeleton of the body, undergoes continuous active turnover, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 197 publications
1
34
0
2
Order By: Relevance
“…In addition, lipids and their derivatives can activated osteoblasts via selective lipid receptors and catabolic enzymes for the internalization and utilization of circulating lipids. Dyslipidaemia and lipid homeostasis disruption can impair osteoblast function and accelerate osteoclast activity 5,6 . Targeting lipid metabolism with a statin has been shown to improve bone density and quality in metabolic bone diseases 7 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, lipids and their derivatives can activated osteoblasts via selective lipid receptors and catabolic enzymes for the internalization and utilization of circulating lipids. Dyslipidaemia and lipid homeostasis disruption can impair osteoblast function and accelerate osteoclast activity 5,6 . Targeting lipid metabolism with a statin has been shown to improve bone density and quality in metabolic bone diseases 7 …”
Section: Introductionmentioning
confidence: 99%
“…Despite all the analysis carried out in this study, we can consider as a limitation the failure to perform an immunohistochemical analysis, which would favor the understanding of bone formation. Furthermore, it could be associated with metabolic dysfunction with alcohol consumption and its influence on the bone repair process [51,52]. There is a need for further studies as the number of patients who receive orthopedic and dental procedures, and who chronically use alcoholic beverages, has increased considerably.…”
Section: Discussionmentioning
confidence: 99%
“…To sustain a suitable blood calcium level, bones may breakdown and bring calcium into the blood [33]. Therefore, bone may be porous and prone to fractures [31,[34][35]. In addition, recent research also found hypertension corresponded with the low level of 25-hydroxy vitamin D and osteocalcin, which leaded to a low bone turnover [11].…”
Section: Discussionmentioning
confidence: 99%